PENGARUH JUMLAH PRODUKSI, HARGA INTERNASIONAL DAN NILAI TUKAR TERHADAP EKSPOR KERTAS INDONESIA - Dewi, Made Febby Anggia; Indrajaya, I Gusti Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2020)
I ndonesia as a paper producing country must be able to show market developments so that the sustainability of the industry and the country's economy becomes more advanced. The purpose of this study is to analyze the effect of total production, international prices and exchange rates on Indonesian paper exports. The type of data used is secondary data. Data collection is done through non-behavioral observation methods. The analysis technique used is multiple linear regression using quarterly data from 2008-2017. The results showed that the variable amount of production, international prices, and exchange rates had a simultaneous and significant effect on Indonesian paper exports. The results of the t test showed that the variable amount of production had a positive and significant effect on Indonesian paper exports. International prices and exchange rates have a negative and not significant effect on Indonesian paper exports. Keywords: Exports, Amount of Production, International Prices, Exchange Rates